Current Account Sustainability : Selected East Asian and Latin American Experiences - Razin, Assaf; Milesi-Ferretti, Gian. (Washington, D.C. : International Monetary Fund, 1996)
A number of developing countries have run large and persistent current account deficits in both the late seventies/early eighties and in the early nineties, raising the issue of whether these persistent imbalances are sustainable. This paper puts forward a notion of current account sustainability and compares the experience of three Latin American countries-Chile, Colombia Mexico-and three East Asian countries-Korea, Malaysia and Thailand. It identifies a number of potential sustainability indicators and discusses their usefulness in predicting external crises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet